2021
DOI: 10.1093/heapro/daab174
|View full text |Cite
|
Sign up to set email alerts
|

E-health literacy levels of high school students in Turkey: results of a cross-sectional study

Abstract: Summary Digital health literacy is defined as the ability to search, find, and understand health information available on electronic resources and to use the information obtained from these resources to address a health problem. This study aimed to identify the digital health literacy levels of high school students and the factors that contribute to its development. This cross-sectional study was conducted with 1250 high school students from 10 high schools. The data were collected using the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
1
13
0
7
Order By: Relevance
“…At the enabling characteristics, preference, attitude, frequency, and access to online health knowledge-seeking were explored to be the main influencing factors. Our findings showed that having access to the Internet or a mobile device plays a crucial role in the ability to acquire and evaluate health-related information, which has been reported by a number of studies [ 16 , 29 , 30 ]. Recently, smartphones have become the main device to access the Internet, which allows participants to look for health symptoms and health-related factors at any time and to have a higher level of e-health literacy [ 62 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…At the enabling characteristics, preference, attitude, frequency, and access to online health knowledge-seeking were explored to be the main influencing factors. Our findings showed that having access to the Internet or a mobile device plays a crucial role in the ability to acquire and evaluate health-related information, which has been reported by a number of studies [ 16 , 29 , 30 ]. Recently, smartphones have become the main device to access the Internet, which allows participants to look for health symptoms and health-related factors at any time and to have a higher level of e-health literacy [ 62 ].…”
Section: Discussionsupporting
confidence: 61%
“…Among the elderly in China, the status quo of e-health literacy was low and the influencing factors include age, gender, educational level, marital status, and cultural barriers [ 15 ]. Research in Turkey has shown that the mean score of e-health literacy in high school students was high and the association between family structure, knowing the importance of health, easy access to the Internet, highly educated parents, and e-health literacy, was found [ 16 ]. According to a study by David Ka-Ki Wong et al, e-health literacy among primary care patients in Hong Kong can be predicted by a variety of demographic and behavioral factors, including age, better self-rated health, more frequent Internet use, more frequent online health information seeking, and a wider variety of health information websites [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a Philippines study found eHealth literacy level (at 32.45) was higher among adolescents [28]. In a Turkish study, the mean score was 27.5 [29]. Comparison of the findings with those of other studies confirms that as proficient users of the internet, adolescents have a moderate level of eHealth skills.…”
Section: Discussionmentioning
confidence: 49%
“…In this study, adolescents' ehealth literacy level was found to be relatively high and acceptable with scores of 29.40±6. 29. In a study conducted in China, the eHealth scores of adolescents were found to be above 30 [26] and in Korean adolescents it was reported 3.59 as item mean [27].…”
Section: Discussionmentioning
confidence: 95%
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%